2006
DOI: 10.1186/1477-7517-3-35
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the dissemination of four harm reduction strategies: a survey of addiction treatment providers in Ontario

Abstract: A sample of service providers at addictions agencies' in Ontario were interviewed by telephone to assess attitudes toward, anticipated internal and external barriers to implementing, and expected benefits of four harm reduction strategies: needle exchange, moderate drinking goals, methadone treatment, and provision of free condoms to clients. Respondents were also asked to define harm reduction, list its most important elements, and describe what they find most troubling and most appealing about harm reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Our findings are both supported and contradicted by an Ontario exploration of barriers to the dissemination of harm reduction (Hobden & Cunningham, 2006). Like the Ontario study, we found that there was little consensus in defining harm reduction or its core elements.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Our findings are both supported and contradicted by an Ontario exploration of barriers to the dissemination of harm reduction (Hobden & Cunningham, 2006). Like the Ontario study, we found that there was little consensus in defining harm reduction or its core elements.…”
Section: Discussionsupporting
confidence: 50%
“…Only 28% of inpatient, correctional and detoxificationbased programs supported nonabstinence goals (Rosenberg et al, 1996). Furthermore, although Hobden and Cunningham's (2006) findings showed that Ontario service providers strongly supported moderate drinking goals, there was no consensus about what constitutes harm reduction or any elaboration on the provision of moderate drinking services which continues to be significant gaps in service delivery. 1 A growing focus on managed drinking in Canada has begun to emerge, specifically addressing the needs of those with a coexisting housing instability and severe drinking problem, resulting in the creation and study of more concretely developed programming around managed or controlled drinking programs than we have seen to date (Pauly et al, 2018;Stockwell et al, 2018;Vallance et al, 2016).…”
Section: The Influence Of Dominant Addiction Discoursementioning
confidence: 93%
See 1 more Smart Citation
“…Addressing community concerns is particularly important as one Canadian study found that the anticipated community resistance to harm reduction was the biggest barrier for service providers to implementing harm reduction programming [40]. This anticipated concern has been quantified in our study as overall support for community needle distribution was lower than general needle distribution.…”
Section: Discussionmentioning
confidence: 88%
“…A study in Russia reported major challenges in service provision for drug users, including lack of resources, rehabilitation programs, and social support (10). Another study of service providers in Canada identified potential barriers to implementing harm reduction strategies, including lack of staff and funding, as well as anticipated staff resistance (11).…”
Section: Introductionmentioning
confidence: 99%